We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
67
2
avatar+153 

deleted

 Oct 17, 2019
edited by SoulSlayer615  Oct 23, 2019
 #1
avatar
+1

Solve for x:
sqrt(x^2) = 6

Raise both sides to the power of two:
x^2 = 36

Take the square root of both sides:

 x = 6       or        x = -6

 Oct 17, 2019
 #2
avatar+104869 
+1

√[4x^2]  - √x^2   =   6

 

We can write this in the following manner

 

l 2x l   -  l x l   =  6

 

2 l x l   -  ; x l   =   6

 

l x l   =   6

 

This is true when  x  = 6  or x  = - 6

 

cool cool cool

 Oct 18, 2019

35 Online Users

avatar
avatar
avatar
avatar
avatar